2018
DOI: 10.1108/jmtm-09-2017-0196
|View full text |Cite
|
Sign up to set email alerts
|

Leanness assessment of organizational performance: a systematic literature review

Abstract: Purpose The purpose of this paper is to review various themes of leanness, leanness assessment approaches, leanness assessment areas, and their evolution by a systematic literature review (SLR). Design/methodology/approach The eight types of literature review methodologies are identified and compared. The SLR is selected after critically analyzing the eight types of literature reviews. A four-phased SLR (i.e. plan, do, analyze/synthesize, and propose) has been carried out based on the peer-reviewed journal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
68
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(72 citation statements)
references
References 92 publications
3
68
0
1
Order By: Relevance
“…Second, and maybe the most powerful contribution of this research: in presence of Supply Chain Flexibility, the direct effect of Lean Production on business performance and Mass Personalization is totally eclipsed (overshadowed). Although this finding is new in the literature, it does not contradict prior studies that found a direct effect between Lean Production and business performance (Lamming, 1996;Mason-Jones and Towill, 1999;van der Vaart et al, 2012;Negrão et al, 2017;Sangwa and Sangwan, 2017) nor those that found a direct link between Lean Production and Mass Personalization (Boynton et al, 1993;Stump and Badurdeen, 2012). On the one hand, regarding the (2020), is that LSCM and Supply Chain Flexibility would be two closely interwoven constructs as LSCM provides flexibility to the supply chain; therefore, both constructs have a similar role by overshadowing the direct effect of Lean, at an internal level, on performance.…”
Section: Theoretical Contributionsupporting
confidence: 57%
See 1 more Smart Citation
“…Second, and maybe the most powerful contribution of this research: in presence of Supply Chain Flexibility, the direct effect of Lean Production on business performance and Mass Personalization is totally eclipsed (overshadowed). Although this finding is new in the literature, it does not contradict prior studies that found a direct effect between Lean Production and business performance (Lamming, 1996;Mason-Jones and Towill, 1999;van der Vaart et al, 2012;Negrão et al, 2017;Sangwa and Sangwan, 2017) nor those that found a direct link between Lean Production and Mass Personalization (Boynton et al, 1993;Stump and Badurdeen, 2012). On the one hand, regarding the (2020), is that LSCM and Supply Chain Flexibility would be two closely interwoven constructs as LSCM provides flexibility to the supply chain; therefore, both constructs have a similar role by overshadowing the direct effect of Lean, at an internal level, on performance.…”
Section: Theoretical Contributionsupporting
confidence: 57%
“…From the business performance perspective, literature findings indicate that Lean Production implementation could enable organizations to improve their performance at all organizational levels (Womack et al, 1990;Jayaram et al, 2008;Negrão et al, 2017;Sangwa and Sangwan, 2017). Some research shows that Lean Production seeks to decreases the system's variability sources to increase business efficiency (de Treville and Antonakis, 2006;Shah and Ward, 2007;van der Vaart et al, 2012).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…This step is essential as, if the selected literature is inadequate, inappropriate or irrelevant, the contribution of the following phases will be amiss (Sangwa and Sangwan 2018). There are two key aspects in this stage: the choice of search engines and the choice of search word strings (Tranfield, Denyer, and Smart 2003;Denyer and Tranfield 2009).…”
Section: Phase 2 Locating the Studiesmentioning
confidence: 99%
“…This index was developed based on the application of the Graph-Theoretic Approach (GTA) that can measure the degree of lean implementation according to five main lean elements (supplier interface practices, management practices, human resource practices, process practices, and customer interface) and 22 lean sub-elements. Sangwa and Sangwan (2018) presented a conceptual framework based on key performance indicators (KPIs) to measure lean performance. Seven key areas were evaluated in the framework namely: manufacturing process, new product development, human resource management, finance, administration, customer management, and supplier management.…”
Section: Leanness Assessmentmentioning
confidence: 99%